2018
DOI: 10.1002/cam4.1357
|View full text |Cite
|
Sign up to set email alerts
|

Correlating colorectal cancer risk with field carcinogenesis progression using partial wave spectroscopic microscopy

Abstract: Prior to the development of a localized cancerous tumor, diffuse molecular, and structural alterations occur throughout an organ due to genetic, environmental, and lifestyle factors. This process is known as field carcinogenesis. In this study, we used partial wave spectroscopic (PWS) microscopy to explore the progression of field carcinogenesis by measuring samples collected from 190 patients with a range of colonic history (no history, low‐risk history, and high‐risk history) and current colon health (health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 46 publications
4
17
0
Order By: Relevance
“…Elevated D is a hallmark of cancer cells and has been reported through multiple lines of work using Partial-Wave Spectroscopic (PWS) microscopy in colorectal, lung, and breast cancers (Subramanian et al, 2009 a ; Gladstein et al, 2018). From a theoretical perspective, the spatial arrangement of chromatin packing affects large-scale gene expression patterns through a number of physical regulators, such as chromatin volume concentration, accessible surface area, and chromatin packing scaling D (Huang et al, 2020; Virk et al, 2020 a ).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated D is a hallmark of cancer cells and has been reported through multiple lines of work using Partial-Wave Spectroscopic (PWS) microscopy in colorectal, lung, and breast cancers (Subramanian et al, 2009 a ; Gladstein et al, 2018). From a theoretical perspective, the spatial arrangement of chromatin packing affects large-scale gene expression patterns through a number of physical regulators, such as chromatin volume concentration, accessible surface area, and chromatin packing scaling D (Huang et al, 2020; Virk et al, 2020 a ).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, some studies showed the etiologic field effect models which is the exposures and genetic factor promote tissue microenvironment of cancer and suggest that exposure may be associated with cancer progression. 24 , 25 Smoking is considered one of the exposures and it influences multiple phases of tumor evolution. Therefore, past report supported that smoking may promote microenvironment of lungs, and causes pulmonary metastases of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…31) also detect structural changes with nanoscale sensitivity. PWS, for example, measures interference between scattering from within the cell and the strong reflection from the cell surface-with its varying surface topography-to quantify the disorder strength of cellular mass density (32), whereas CLASS models subcellular size distributions within the cell by averaging light back-scattered from within a confocal volume. Unlike these modalities, nanoNAM uses a stable and sample-independent reference signal to obtain the spectral interference signal from which it extracts 3D depth-resolved intrinsic nuclear architectural properties after mapping it to the optical space via Fourier mapping.…”
Section: Discussionmentioning
confidence: 99%